Prototipagem virtual, simulação e controle de um quadrirotor utilizando controle seguidor com atribuição de autoestrutura completa - Malaquias, Wanderlei (2017)
This dissertation presents the development of a tracking control system, with state feedback, for a didactic plan of a quadrirotor constituted of four rotors arranged in a cross shape. The dynamics system is nonlinear and multivariable, the plant can be set up with two and three degrees of freedom, enabling to study the movements of roll, pitch and yaw. The mathematical models system were generated by virtual prototyping method, with the aid of the dynamic analysis software MSC ADAMS. Two models were generated for each plant configuration, a linear and a nonlinear. The linear model was employed to generate the gain matrix used in the state feedback control system with entire eigenstructure assignment, the nonlinear model represents the dynamics real plant. The models were simulated using the MATLAB/SIMULINK and MSC ADAMS softwares, step, ramp and sine type inputs were used. Analyzes were performed and it was verified that the control system was able to control the nonlinear system using the gains found through the linear model, since the errors found were considered small. The system also proved to be effective in the presence of white noise.